Rola i formy uczestnictwa społeczności lokalnych w procesie zmian podziału terytorialnego - Kaczmarek, Tomasz (Wydział Prawa i Administracji UAM, 1993)
The article presents main problems of the reform of the territorial division of the state from the point of view of the decision-ma king process. Using subjective and objective criteria, the author analysed various forms of social participation (active and passive) in the said process. Attention was also paid to legal instruments regulating the forms and scope of the participation of local communes in the process of changing the territorial division. The article contains various examples of the role of a human factor in shaping the administrative borderlines in Poland and Western Europe. The last part of the article focuses on the evaluation of the contemporary reform of public administration in Poland, taking as a point of reference the assumptions of the participative reform. The author discusses various forms of social activity in the process of shaping a new territorial structure of the state.
The role and forms of participât ion of local communities in the process of changes in the territorial division